CD44v6-competent tumor exosomes promote motility, invasion and cancer-initiating cell marker expression in pancreatic and colorectal cancer cells - Wang, Zhe; Au, Anja von; Hackert, Thilo; Zöller, Margot (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.10580 Zhe Wang, Anja von Au, Martina Schnölzer, Thilo Hackert, Margot Zöller